2012
DOI: 10.1891/0886-6708.27.3.434
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Self-Esteem as a Mediator of the Relationship Between Sports Participation and Victimization: A Study of African American Girls

Abstract: The purpose of this study that focused on African American high school girls was threefold. First, the relationship of sports participation and victimization was explored. Second, the impact of sports participation on self-esteem was assessed. Third, the role of self-esteem and its disaggregated components (social acceptance, competence, and self-confidence) as mediators of the relationship between sports participation and victimization was examined. In accordance with the sport protection hypothesis, it was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
0
13
1
1
Order By: Relevance
“…Similarly to previous research (Anderson 2002;Carlson et al, 2002;Jezl, Molidor, and Wright, 1996;Papadakaski et al, 2008), we found that self-esteem was ATHLETIC PARTICIPATION AND INTIMATE PARTNER VIOLENCE VICTIMIZATION negatively related to IPVV for both women and men. However, contrary to previous research that found that the returns from sport participation are mediated through self-esteem (Broh, 2002;Taylor et al, 2012), including the potential pathway of self-esteem did little to influence the association between sports participation and IPVV in the present study; sports participation remained a significant predictor and we failed to support Hypothesis 1a. However, the variable of own education fully mediated the association between sports participation and IPVV for women, suggesting that those who attended college are the most likely to participate in sports and the least likely to experience IPVV.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly to previous research (Anderson 2002;Carlson et al, 2002;Jezl, Molidor, and Wright, 1996;Papadakaski et al, 2008), we found that self-esteem was ATHLETIC PARTICIPATION AND INTIMATE PARTNER VIOLENCE VICTIMIZATION negatively related to IPVV for both women and men. However, contrary to previous research that found that the returns from sport participation are mediated through self-esteem (Broh, 2002;Taylor et al, 2012), including the potential pathway of self-esteem did little to influence the association between sports participation and IPVV in the present study; sports participation remained a significant predictor and we failed to support Hypothesis 1a. However, the variable of own education fully mediated the association between sports participation and IPVV for women, suggesting that those who attended college are the most likely to participate in sports and the least likely to experience IPVV.…”
Section: Discussioncontrasting
confidence: 99%
“…Interventions aimed at helping youth remain self-confident in the face of some social rejection may serve adolescents well, particularly since behaviors associated with bullying victimization may also reflect underdeveloped social skills, which may be common among younger students (Taylor, Wamser, Welch, & Nanney, 2012). Two types of school-specific interventions which have experienced positive evaluation outcomes recently are social and emotional learning programs (Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, 2011) and the behavioral ecological model (Dresler-Hawke & Whitehead, 2009).…”
Section: Implications For School Nursingmentioning
confidence: 99%
“…Although limited, there is a small but growing literature on dating violence victimization stemming from mental health sequelae. For example, work by Taylor, Wamser, Welch, and Nanney (2012) has looked at the role of protective factors and in particular participation in athletics and self-esteem. Drawing on data from a sample of African American students, they examined self-esteem, including the elments of social acceptance, competence, and self-confidence within the etiology of victimization.…”
Section: Introductionmentioning
confidence: 99%